2015
DOI: 10.13141/jflr.v1i1.251
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of sustainable forest management: an application of the triple perspective typology of stakeholder theory in a case study in Sabah, Malaysia

Abstract: The progress of the concept of Sustainable Forest Management (SFM) is dynamic and its success or failure during implementation can be evaluated in different ways. In a detailed survey in four Forest Management Units (FMUs) in Sabah, the current implementation of SFM at the FMU level was assessed based on the triple perspective typology of stakeholder theory. This approach encompasses conceptual, corporate and stakeholder centric point of view. The conceptual perspective explores the SFM concept and how it rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In Sabah, SFM was first adopted state wide in 1997 following the successful SFM model implemented in Deramakot Forest Reserve (certified by Forest Steward Council), which demonstrated that SFM with a logging component is compatible with wildlife management (Tongkul et al 2013;Lintangah and Weber 2015). SFM is implemented in Forest Management Unit (FMU) areas managed by private companies that have acquired a Sustainable Forest Management License Agreement (SFMLA) license or by the state government for forest reserves (Figure 1).…”
Section: Sustainable Forest Management (Sfm) and Social Forestry (Sf)mentioning
confidence: 99%
“…In Sabah, SFM was first adopted state wide in 1997 following the successful SFM model implemented in Deramakot Forest Reserve (certified by Forest Steward Council), which demonstrated that SFM with a logging component is compatible with wildlife management (Tongkul et al 2013;Lintangah and Weber 2015). SFM is implemented in Forest Management Unit (FMU) areas managed by private companies that have acquired a Sustainable Forest Management License Agreement (SFMLA) license or by the state government for forest reserves (Figure 1).…”
Section: Sustainable Forest Management (Sfm) and Social Forestry (Sf)mentioning
confidence: 99%